Pengaruh Konsentrasi Natrium Benzoat dan Lama Penyimpanan terhadap Waktu Respon Lakmus Organik Ekstrak Bunga Telang - Hasyimiyyah, Amany; Kusumantoro, Heribertus Rudi; Pratama, Yoga Putra (Fakultas Teknik UMSU, 2025)
The butterfly pea flower contains anthocyanins that function as natural pH indicators but are prone to fungal growth. This study aimed to investigate the effect of sodium benzoate concentration and storage duration on the response time of bio litmus paper made from butterfly pea (Clitoria ternatea) flower extract. Sodium benzoate was added as an antifungal agent at concentrations of 0%, 1%, 2%, and 3%. Samples were stored for 0, 7, and 14 days, then tested for response time and fungal contamination. Results showed that only samples without sodium benzoate exhibited fungal growth after 14 days. Storage for 7–14 days improved response time efficiency. ANOVA analysis indicated that sodium benzoate concentration, storage duration, and their interaction significantly affected response time. This study demonstrates that sodium benzoate addition and proper storage can enhance the effectiveness and stability of butterfly pea-based bio litmus paper as a natural pH indicator.